We are to find the equation of the line joining the points
![(-3,-3),(12,2)](https://img.qammunity.org/2023/formulas/mathematics/college/1aysoxear0mdwbe5lyjosbfq8m4rghff2r.png)
The equation of a line is given as
![(y-y_1)/(x-x_1)=(y_2-y_1)/(x_2-x_1)](https://img.qammunity.org/2023/formulas/mathematics/college/3wt52xf3n7hjhwt6qolt0l02t41489sre0.png)
From the given points we have
![\begin{gathered} x_1=-3,x_2=12 \\ y_1=-3,y_2=2_{} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/j0y68u9wg7c926bt8g43leosell9haz9oj.png)
Therefore, the equation of the line is
![(y-(-3))/(x-(-3))=(2-(-3))/(12-(-2))](https://img.qammunity.org/2023/formulas/mathematics/college/3zgvv6ey2yjn7mh1y7ek8kur0txakauzud.png)
This gives
![(y+3)/(x+3)=(2+3)/(12+3)](https://img.qammunity.org/2023/formulas/mathematics/college/b7yg0timeuprfm6q570yvqwjlz8qzksoa9.png)
Simplifying this we have
![\begin{gathered} (y+3)/(x+3)=(5)/(15) \\ (y+3)/(x+3)=(1)/(3) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/gvccl1lrw81e0xnp6qh43sm8z4k4ye32hj.png)
This further gives
![\begin{gathered} 3(y+3)=x+3 \\ 3y+9=x+3 \\ 3y=x+3-9 \\ 3y=x-6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/xj7ptkbhse0840cttqesvwkeobufobfjgr.png)
Dividing both sides by 3 we get
![\begin{gathered} y=(1)/(3)x-(6)/(3) \\ y=(1)/(3)x-2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/12oicpsioaxmk232di59f7ytevldtzetw6.png)
Therefore, the equation is
![y=(1)/(3)x-2](https://img.qammunity.org/2023/formulas/mathematics/college/blbebwlyi1wew78bdghh3u9wl3sie4eruh.png)